Japanese Food Supply Chain Management Issues in Malaysia: Secrets Reveal - Saidon, Intan Marzita; Mat Radzi, Rafisah; Ab Ghani, Nadzri (International Journal of Supply Chain Management, 2018)
There is an equivocal claim that Japanese companies are better at managing their supply chains. Yet, little is known about the Japanese supply chain, particularly the food supply chain. Using a qualitative approach, twenty interviews with supply chain managers were conducted. Evidence suggests that a short and simple structure is a platform of the food supply chain and there exists a different level of integration along the chain. There are five main risks attached along the chain and the companies employ various practices to mitigate those risks. Conclusions are presented along with limitations and future research directions.